Mentorship Programme for Undergraduate Medical Students - Daha, Sunil Kumar; Regmi, Saurav; Dahal, Saurab; Jha, Rishi Raj; Mandal, Rajesh Kumar (Journal of Nepal Health Research Council, 2023)
Background: Mentorship is seen as a continuous journey of discovery, shared learning, and personal and professional development to achieve leadership and excellence. Medical schools can be monitored with respect to the provision of mentorships as a quality characteristic. So, the aim of our study was to know the prevalence and the impact of mentorship program in medical schools of Nepal and the need of this program in medical schools all over Nepal. Methods: A descriptive cross-sectional study was conducted among medical students in medical schools in Nepal. Ethical approval from the Nepal Health Research Council (NHRC) was obtained (Ref. 667). The cumulative data obtained nationwide was entered in computerized spreadsheet software (Microsoft Excel) and analyzed using MS Excel and SPSS 16.0. Results: Patan Academy of Health Sciences (PAHS) 131 (50.8%) had highest prevalence of mentorship program. Out of 258 students, 110 (42.6%) knew that there was mentorship program in their medical schools. The study found the role of mentors in building rapport with faculties (61.82%), developing professional skills (81.82%) and learning evidence-based medicine (74.55%). 98.8% participants soughed for the need of this program in their medical schools. Conclusions: The prevalence of mentorship program among medical school in Nepal was found to be low. Individuals involved in the mentor-mentee relationship found the role of mentor not only on academics but also on their personal and social enterprises. Medical students who were familiar with the concept of this program reported its need in medical school. Keywords: Medical students; mentor; mentorship program